SIMULASI OPTIMALISASI PRODUKSI KAIN TENUN DALAM MENINGKATKAN LABA BISNIS DI PT. ARGO PANTES TANGERANG - Harianto, Raden Achmad (E-Journal Widya Ekonomika, 2020)
Corporate performance is measurable by its activities of which is supported by the industrial performance through the optimization in targeted profit. PT. Argo Pantes is a manufacturing company which processes yarn and woven fabric. In the daily process the company has many problems or constrains in production planning. Uncertainity of the demand of goods fluctuation has effect on shortage or Surplus production. Others problems are raw materials, machine work hour, labour work hour, spindle hour per unit, Loom hour per unit, and the demand of the products. The objective of this research is to maximize a business profit by using the Application of Linear Programming. Simplex method of this linear programming purposes to maximize profit in linear function, where Profit (Z) = 20 X1 + 15 X2 and linear function of the two constrains, Spindle hour per unit : 100 X1 + 50 X2 â‰¤ 1000 and Loom hour per unit : 20 X 1 + 25 X 2 â‰¤ 300. The result of the study of the Analysis show that the total profit earned by PT. Argo Pantes at Tangerang to produce a T/C woven fabric is $133.400,- and for cotton 100% woven fabric is $100.050. with the assumtion of profit is in accordance with fixed objective and constrain function.